IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF, LANGSUNG, DAN TIDAK LANGSUNG - Sriliza Sriliza; Siti Zarina; Jumadi Jumadi (CV. Adiba Aisha Amira, 2025)
This study aims to investigate the implementation of active, direct, and indirect learning strategies at the elementary school level. The problem addressed is the effectiveness of these strategies in improving student learning outcomes and engagement. Employing a quantitative research methodology, data was collected through (specify data collection methods, e.g., questionnaires, surveys, observations, tests) from elementary school students. The results indicate that the combination and appropriate application of active, direct, and indirect learning strategies significantly contribute to [state key findings, e.g., enhanced student participation, better understanding of concepts, improved academic performance] in elementary school settings. This research provides insights into how these varied instructional approaches can be effectively integrated to foster a more dynamic and productive learning environment for young learners.